Caffeic acid and its derivatives as heme oxygenase 1 inducer in Hep G2 cell line - Jaikang C. (2014)
Effect of 10, 50 and 100 μg/ml caffeic acid and its esters and amides derivatives on heme oxygenase 1 (HO-1) activity induction in Hep G2 cell line was studied. It was found that caffeic acid ester derivatives could induce HO-1 activity more than amide derivatives. The longer side chain and aromatic side chain affected HO-1 activity. At 10 μg/ml concentration, phenylmethyl 1-(3', 4'-dihydroxyphenyl) propenate (PMDP) had 2.1-fold more activity when compared with control. At 50 and 100 μg/ml concentrations, phenylethyl 1-(3', 4'-dihydroxyphenyl) propenate (PEDP) was the highest HO-1 inducer, whose activity was 2.1- and 2.3-fold greater, respectively, when compared with the control group. Caffeic acid and all derivatives induced HO-1 activity on a higher level than curcumin, positive control. This study implied that caffeic acid and its derivatives could be used to induce HO-1 to protect tissues against free radicals. © 2010 Academic Journals.